STRATEGI PEMASARAN GLOBAL SAMSUNG MENGGUNAKAN CELEBRITY ENDORSEMENT “BTS” DI INDONESIA TAHUN 2020-2024 - Saniyyah Putri Ramadhan; Resa Rasyidah (POLITEKNIK LP3I JAKARTA, 2025)
Samsung Electronics Co., Ltd. is a leading technology company from South Korea that has played a significant role in the global smartphone industry. Samsung's market success is closely related to its international marketing strategies as a multinational corporation seeking to penetrate the Indonesian market. The widespread influence of Korean culture in Indonesia has contributed to its positive reception among the public, leading to the phenomenon known as the 'Korean Wave.' This cultural phenomenon, with its far-reaching impact, has significantly shaped Samsung's marketing strategy. The impact of the Korean Wave has made Korean cultural elements widely adopted for product promotion in various industries, including the smartphone sector. Samsung is one of the companies that are leveraging this cultural phenomenon to enhance its promotional efforts. This study analyzes Samsung Electronics' global marketing strategy in Indonesia, focusing on celebrity endorsement, particularly its collaboration with K-Pop group Bangtan Sonyeondan (BTS) from 2020 to 2024. Using a descriptive qualitative research method, this study collects data and applies the theories of global marketing strategy, the marketing mix, and celebrity endorsement. The findings indicate that Samsung actively promoted its products alongside BTS from 2020 to 2024, utilizing social media campaigns and offering exclusive incentives for certain smartphone purchases.